Internship in Bella Cucina as Marketing & Operations Intern - Agarwal, Aaryan (ATLAS SkillTech University, 2024)
During my enriching two-month internship at Bella Cucina Mumbai, I had the privilege to delve into the dynamic realms of marketing, operations, and business development within the culinary industry. This executive summary outlines the key experiences, learning outcomes, and contributions I made during my time as a marketing and operations intern. The marketing component of my internship provided a comprehensive understanding of the strategies employed to promote a high-end culinary establishment. Under the guidance of the marketing team, I actively participated in crafting and executing social media campaigns, planning an executable loyalty program, managing digital content, and analyzing customer engagement metrics. By using various analytical tools, I gained valuable insights into customer preferences, which were instrumental in refining marketing efforts to enhance brand visibility and attract a wider audience.
Project Report on Internship in Bella Cucina as Marketing & Operations Intern (2022-24) Under the Guidance of Prof. Sukanya Dikshit
Keywords: Marketing; Operations; Business Development; Analysis; Digital Content